2017
DOI: 10.3390/molecules22111860
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Polymers Containing 1,3-Phenylenebis-((1H-1,2,4-triazol-1-yl)methanone) Ligand: Synthesis and ε-Caprolactone Polymerization Behavior

Abstract: The reaction of isophthaloyl dichloride with 1H-1,2,4-triazole afforded the new ligand 1,3-phenylenebis(1,2,4-triazole-1-yl)methanone (1). A series of Co(II), Cu(II), Zn(II) and Ni(II) complexes were synthesized using 1 and then characterized by melting point analysis, elemental analysis, theoretical calculations, thermogravimetric analysis, X-ray powder diffraction, nuclear magnetic resonance, infrared and Raman spectroscopy. Experimental and computational studies predict the formation of coordination polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Therefore, these polymers could be applied or implemented in the design of biodegradable packaging [42]. In general, the PCLs obtained showed a lower dispersion, a higher molecular weight and high degrees of crystallinity compared with other polycaprolactones obtained using previously reported metal catalysts by the authors’ research group and PCLs that are commercially available [9,10,13,16,42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these polymers could be applied or implemented in the design of biodegradable packaging [42]. In general, the PCLs obtained showed a lower dispersion, a higher molecular weight and high degrees of crystallinity compared with other polycaprolactones obtained using previously reported metal catalysts by the authors’ research group and PCLs that are commercially available [9,10,13,16,42].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ancillary ligands can modify metal complexes that then favor the polymerization of lactones [12,13]. In some cases, pyrazolyl, triazole, and pyrazole derivatives act as nitrogen-donor ligands and therefore increase the Lewis acidity of the metal to enhance the coordination to the lactone [14,15,16]. Specifically, the combination of nitrogen- and oxygen-donor ligands produce active Zn(II) and Cu(II) complexes for the ROP of ε-caprolactone [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…While the C�O peak in the ligand was seen at 1731 cm −1 , these bonds in the Co(II), Ni(II), and Zn(II) metal complexes were observed at 1723, 1727, and 1723 cm −1 , respectively. ese bands, depending on the formation of the complexes, have shifted to a lower wave number, whereby those results indicated the lower rigidity of the C�O bands in the ligand [25]. e change in the color of the complexes was caused by the orbital transition, namely, the change in the energy of the orbitals, which pointed out that metal complexes were formed.…”
Section: Journal Of Chemistrymentioning
confidence: 92%
“…Moreover, DFT calculations enable the characterization of the electron transfer mechanism in cocrystals involving 3,5-DNBA units and [{Zn(L)(DMF) 4 }·2BF 4 ] α (L = N 2 ,N 6 -di(pyridin-4-yl)naphthalene-2,6-dicarboxamide), in addition to the resulting HOMO-LUMO and bandgap values [ 98 ]. The results show that the LUMO position can be tuned to accept the incoming electron from π-electron-rich ligands.…”
Section: Theoretical Study Of 35- and 24-dinitrobenzoate Metal Complexesmentioning
confidence: 99%